Komunikasi Interpersonal Orang Tua dengan Anak Broken Home (Studi pada Perumahan Villa Permata Sunggal) - Aulia Farhan; Sori Monang; Abdul Karim Batubara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
At the Villa Permata Sunggal Housing, this study attempts to determine the nature and impact of interpersonal communication between parents and children from a broken household. The manner of communication and the function of parents in the lives of children from broken homes must be addressed immediately. The findings of this study show that communication is going well since people are paying attention to each other and communicating effectively. This method of communication has a number of consequences. First, a youngster from a broken home who communicates in a harmonious manner has both harmful and positive consequences. Second, children who grow up in broken homes with poor communication tend to be deviant. Parents should commit time to their children by interacting with them and engaging in direct connection with them. The principle of self-disclosure and SOR are used in this work, as well as descriptive methodologies. In-depth interviews and observation are two data collection approaches utilized by researchers. Three harmonious broken households, three disharmonious families, and two harmonious-disharmonious families were questioned by the researchers.